2020
DOI: 10.1063/5.0037360
|View full text |Cite
|
Sign up to set email alerts
|

Insights on drying and precipitation dynamics of respiratory droplets from the perspective of COVID-19

Abstract: We isolate a nano-colloidal droplet of surrogate mucosalivary fluid to gain fundamental insights into airborne nuclei’s infectivity and viral load distribution during the COVID-19 pandemic. The salt-water solution containing particles at reported viral loads is acoustically trapped in a contactless environment to emulate the drying, flow, and precipitation dynamics of real airborne droplets. Similar experiments validate observations with the surrogate fluid with samples of human saliva samples from a healthy s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 56 publications
7
65
0
Order By: Relevance
“…Several researchers (e.g., Refs. 76 and 77 ) studied the effect of evaporation of organic solvents and saltwater droplets on surfaces, while a few others (e.g., Ref. 78 ) studied the evaporation of saliva droplets on surfaces in context with COVID-19.…”
Section: Surfaceborne Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers (e.g., Refs. 76 and 77 ) studied the effect of evaporation of organic solvents and saltwater droplets on surfaces, while a few others (e.g., Ref. 78 ) studied the evaporation of saliva droplets on surfaces in context with COVID-19.…”
Section: Surfaceborne Transmissionmentioning
confidence: 99%
“…It is observed that the acoustic streaming causes an increase in evaporation rate that is comparable to forced convection at a relative velocity of around 0.1 m/s. Basu et al 77 studied the drying and precipitation characteristics of the saltwater droplets in a similar levitator using a shadowgraph technique. He et al 79 used an inverted microscope and a CMOS camera in their experiments and found that during the evaporation, a droplet of size ranging from 5 to 100 μ m shrinks to a few micrometers in size (referred to as residues).…”
Section: Surfaceborne Transmissionmentioning
confidence: 99%
“…32 Even bigger-size droplets may undergo evaporation before landing on a surface/ground and a small droplet-nuclei may be formed, which remains suspended in air, and the virus may still survive therein. 33 Notably, previous virus titer measurements [dose 50% tissue-culture infectious dose (TCID 50 ) per milliliter] 34 disclosed that the coronavirus can sustain for hours in aerosols. It is, therefore, clear that the six-feet social distancing norm alone is not sufficient to curb disease spread via the airborne route.…”
mentioning
confidence: 99%
“…Airborne transmission of virus-containing saliva droplets produced by speaking, coughing, or sneezing is one of the well-known [ 1 , 2 ] mechanisms that play a crucial role in the spread of numerous infectious diseases, such as influenza [ 3 , 4 ] and SARS-CoV-2 [ [5] , [6] , [7] , [8] ]. When a saliva droplet evaporates to a so-called droplet nucleus, which is a small particle with much reduced water content [ 9 ], it can remain suspended in air for a long time. According to current WHO guidelines, the term droplet nucleus refers to droplets with radii smaller than [ 10 ].…”
Section: Introductionmentioning
confidence: 99%